Support for young people who are distressed by hearing voices: protocol for an uncontrolled feasibility evaluation of a psychological intervention package delivered within secondary schools (the ECHOES study) - Mark Hayward; Mary John; Sarah Parry; Anna-Marie Bibby-Jones; Faith Orchard; Fiona Malpass; Clare Dixon; Akira Naito (Pilot and Feasibility Studies)
Abstract Background Hearing voices is a common experience for young people and can cause significant distress. There are no evidence-based psychological interventions for distressing voices in young people, although a focus on coping strategies has been suggested as a useful approach. We have developed and evaluated a brief 1:1 coping intervention for young people who hear distressing voices. This intervention has been successfully piloted within Child and Adolescent Mental Health Services (CAMHS), together with a psychoeducational workshop for parents. The 1:1 intervention and the workshop will be combined into an intervention package and offered within schools to maximise accessibility. Methods This study will be an uncontrolled feasibility evaluation addressing the following questions: is the intervention package acceptable to young people, those who support them, and staff and practitioners within secondary schools? What is the optimum content, structure, and duration for the intervention package? Is delivery of the intervention package feasible for the practitioners and what are their requirements for training and supervision? What tools can be used to evaluate the impact of the intervention package? The study will be guided by the MRC Framework for the development of complex interventions and consist of an iterative process over four phases: phase 1—adaptation of the intervention package with young people, parents, and school staff; phase 2—delivery of the intervention package through Mental Health Support Teams to students, supporters who have been nominated by the students and school staff; phase 3—analysis of quantitative and qualitative data collected from participants and practitioners; phase 4—further adaptation of the intervention package with young people, parents and school staff. Discussion If the findings from the study suggest that a future trial is warranted, a feasibility Randomised Controlled Trial will be designed to establish the parameters for a definitive trial. Trial registration Current Controlled Trials ISRCTN registration number: 16395888. Registered on 11 January 2024. 10.1186/ISRCTN16395888.